EVOLUTION OF ACCREDITATION SYSTEM IN RUSSIAN HIGHER EDUCATION - G. N. Motova (Высшее образование в России)
The article focuses on the main principles, forms and approaches to education quality evaluation in the process of establishing and developing the system of state accreditation of educational institutions and study programmes in Russian higher education. In the author's opinion, the transformation process of accreditation forms during the last 20 years was conditioned by the changes in the state education policy. Based on the analysis of the practice of establishing the state and independent systems of quality assurance, their specific features and diversity of forms, the article discusses the opportunities and prospects of further development of the quality assurance system.